Biofilms of Pathogenic Nontuberculous Mycobacteria Targeted by New Therapeutic Approaches - Aung, Thet Tun (2016)
Microbial infections of the cornea are potentially devastating and can result in permanent visual loss or require vision-rescuing surgery. In recent years, there has been an increasing number of reports on nontuberculous mycobacterial infections of the cornea. Challenges to the management of nontuberculous mycobacterial keratitis include delayed laboratory detection, low index of clinical suspicion, poor drug penetration, slow response to therapy, and prolonged use of antibiotic combinations. The ability of nontuberculous mycobacteria to evade the host immune response and the ability to adhere and to form biofilms on biological and synthetic substrates contribute to the issue. Therefore, there is an urgent need for new antimicrobial compounds that can overcome these problems. In this study, we evaluated the biofilm architectures for Mycobacterium chelonae and Mycobacterium fortuitum in dynamic flow cell chamber and 8-well chamber slide models. Our results showed that mycobacterial biofilms were quite resistant to conventional antibiotics. However, DNase treatment could be used to overcome biofilm resistance. Moreover, we successfully evaluated a new antimicrobial compound (AM-228) that was effective not only for planktonic mycobacterial cells but also for biofilm treatment and was compared favorably with the most successful “fourth-generation” fluoroquinolone, gatifloxacin. Finally, a new treatment strategy emerged: a combination of DNase with an antibiotic was more effective than an antibiotic alone.